Construction and validation of a cell death-related genes prognosis signature of hepatocellular carcinoma - Yue Ma; Che Ismail Che Noh; Rahmawati Pare (AME Publishing Company, 2025)
Background: The cell death pathway, including apoptosis, autophagy, and necroptosis, plays an essential role in hepatocellular carcinoma (HCC) progression and outcome. However, the integration of the three cell death pathways into a prognostic signature has not yet been reported in HCC. This study aimed to investigate the association among cell death-related genes (CDRGs), prognosis, immune microenvironment, and immune checkpoint. Methods: The RNA expression profiles and corresponding clinical data of HCC were retrieved from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), and International Cancer Genome Consortium (ICGC). Univariate Cox regression analysis was performed to identify the relevant prognostic genes, and Lasso Cox regression analysis was employed to calculate the risk score. The relationship between the risk score and clinicopathological characteristics, immune cell infiltration, and immune checkpoint expression was analyzed. Results: A prognostic risk model for HCC was constructed from the identified CDRGs and patients were subgrouped based on risk score. High-risk patients for HCC exhibited a significantly lower overall survival (OS) rate than the low-risk patients. In addition, the receiver operating characteristic (ROC) curve demonstrated the predictive ability of the risk score. Patients in the high-risk group exhibited lower immune cell infiltration and higher expression levels of immune checkpoint molecules. Conclusions: The cell death-related signature established herein provides a valuable predictive tool for survival and holds promise as a potential therapeutic biomarker for HCC.